Upaya Guru Dalam Mengembangkan Kecerdasan Interpersonal Anak Usia Dini - Sembiring, Juraidah Br.; Nasution, Annisa Zakia; Hayati, Rafiqah; Nashfati, Fadiah Dian; Nasution, Fauziah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Interpersonal intelligence in early childhood is important to support children’s ability to socialize, cooperate, and build healthy social relationships. This type of intelligence is not innate but can be developed through early stimulation, especially by teachers in educational environments. This study uses a literature review method to examine the role of teachers in developing children’s interpersonal intelligence. The findings show that teachers can stimulate children’s interpersonal intelligence through social activities, empathy learning, communication development, positive reinforcement, and collaboration with parents.